Increased cytomegalovirus immune responses at disease onset are protective in the long-term prognosis of patients with multiple sclerosis. Issue 3 (7th November 2022) - Comabella, Manuel; Tintore, Mar; Sao Avilés, Augusto; Carbonell-Mirabent, Pere; Malhotra, Sunny; Rovira, Alex; Fissolo, Nicolás; Lünemann, Jan D; Montalban, Xavier
Abstract : Objective: It remains unclear whether viral infections interfere with multiple sclerosis (MS) disease progression. We evaluated the prognostic role of antibody responses toward viruses determined at disease onset on long-term disease outcomes. Methods: Humoral immune responses against Epstein-Barr virus (EBV)-encoded nuclear antigen EBNA1, viral capsid antigen (VCA) and early antigen, and toward cytomegalovirus (HCMV), human herpesvirus 6 and measles were investigated in a cohort of 143 patients with MS for their association with long-term disability and inflammation disease outcomes. Results: Median (IQR) follow-up was 20 (17.2–22.8) years. In univariable analysis, increased HCMV levels were associated with a lower risk to Expanded Disability Status Scale 4.0 (HR 0.95; 95% CI 0.91 to 0.99; p=0.03), to develop a secondary progressive MS (HR 0.94; 95% CI 0.90 to 0.99; p=0.02) and to first-line treatment (HR 0.98; 95% CI 0.96 to 0.99; p=0.04). High HCMV IgG levels were associated with a longer time to first-line treatment (p=0.01). Increased immune responses against EBV-VCA were associated with higher risk for first-line (HR 1.45; 95% CI 1.12 to 1.88; p=0.005) and second-line treatments (HR 2.03; 95% CI 1.18 to 3.49; p=0.01), and high VCA IgG levels were associated with shorter time to first-line (p=0.004) and second-line (p=0.02) therapies. EBNA1-specific IgG levels correlated with disease severity (0.17; p=0.04) and with an increased relapse rate during follow-up (relapse rate 1.26; 95% CI 1.03 to 1.56; p=0.02) that remained stable in multivariable analysis. Conclusions: These results indicate that elevated immune responses against HCMV at disease onset have protective effects on long-term disability and inflammation disease outcomes. Our data also indicate that increased immune responses against EBV in early phases may influence long-term disease prognosis.